Air Transport versus High-Speed Rail: An Overview and Research Agenda - Xiaoqian Sun; Yu Zhang; Sebastian Wandelt (Journal of Advanced Transportation)
The development of high-speed rail (HSR) services throughout the last decades has gradually blurred the concept of competition and cooperation with air transportation. There is a wide range of studies on this subject, with a particular focus on single lines or smaller regions. This article synthesizes and discusses recently published studies in this area, while aiming to identify commonalities and deviations among different regions throughout the world, covering services from Europe, Asia, and North America. Our meta-analysis reveals that the literature is highly controversial and the results vary substantially from one region to another, and a generalization is difficult, given route-specific characteristics, such as demand distribution, network structure, and evolution of transportation modes. As a major contribution, we propose a list of five challenges as a future research agenda on HSR/air transport competition and cooperation. Among others, we see a need for the construction of an open-source dataset for large-scale multimodal transport systems, the comprehensive assessment of new emerging transport modes, and also taking into account the resilience of multimodal transport systems under disruption.